Attitudes and behaviour of Nigerian university students towards voluntary HIV counselling and testing (2009)
Despite increased campaign for voluntary counselling and testing (VCT) for HIV/AIDS in Nigeria only a negligible number of young people participates in this activity. This study investigates the factors affecting the attitudes and behaviour of students at the University of Ibadan, which is a microcosm of other universities in the country, as a way of understanding the context in which apathy towards VCT occurs. The Health Belief Model and the Theory of Reasoned Action enable the study to highlight the variables that interact to influence students’ behaviour towards VCT. Data were collected through structured questionnaires and in-depth interviews (IDIs). The survey involved 400 respondents selected through a multi-stage sampling technique, while 12 IDIs were conducted among undergraduate and postgraduate students identified as relatively knowledgeable about issues related to VCT – mainly as peer educators. The findings show that although 95.3% of the students were aware of VCT, only 15% of them had undertaken voluntary HIV testing. The specific results indicate that there is a wide gap between intention and action related to VCT. Of the 57.5% respondents who had discussed VCT and intended to participate in it, only 27.3% actually underwent VCT. A combination of overconfidence in not being HIV positive, fear of testing positive to the virus, the perceived non-confidentiality of test results and stigma and discrimination strongly discourage students from partaking in VCT. The study clearly indicates the need to bridge the gap between knowledge and behaviour through vigorous sensitization and enlightenment activities.